If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + b = c + 3a Reorder the terms: 9 + b = 3a + c Solving 9 + b = 3a + c Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + b = 3a + -9 + c Combine like terms: 9 + -9 = 0 0 + b = 3a + -9 + c b = 3a + -9 + c Reorder the terms: b = -9 + 3a + c Simplifying b = -9 + 3a + c
| -2(x-1)=-2x-(x+4) | | 9x-11-2x+4= | | x^2+y^2-12y=0 | | 2-10=z/-7 | | 3x-5y+4y+2x= | | 14x^2-24=0 | | 0=X^4-8x | | y-.333=2.66 | | -3(x-2)+4(x-7)=20 | | u+.333=.333 | | 4x+4(6x+3)= | | -0.55p-5=0.45 | | cosx/2-1=0 | | 7x^4+2x^2+21=0 | | -4-(2y-1)=-(3y+1) | | 21/4=8/t | | 4*(x+6)= | | X(-2)+18=50(-3x)+25 | | 2*(x+3)= | | 2*(3a)= | | -24+x=36 | | (-2x)+5+3x+-4x+(-1)+(-x)= | | 2x+(-2)=17 | | 6*2s=39 | | ×/3-4=×/5-6 | | 2(-1)+y=17 | | Y+12=c | | 3/7=n/21 | | 4.5+x=-2.3 | | 10x-15=6x+14 | | 3(7+2x)=7(x-1) | | ln(5-x)=2.3 |